Building an urban food policy: the case of Cali, Colombia - Isaza Castellano, Ruby; Henry, Guy; Rankin, Sara (Quae, 2022)
This chapter discusses the process of building an Food and Nutrition Security policy in Cali. The conclusion, asks a number of key questions as part of an analysis of the main driving forces behind the successful construction and formulation. The book -Public Policies and Food Systems in Latin America- of which this chapter is a part, presents the results of a collective research effort coordinated by the Public Policy and Rural Development in Latin America network (PP-AL), an inter-institutional platform created in 2011 to enable regional academic and policy dialogue on the design and implementation of rural development policies.